2006
DOI: 10.1111/j.1399-0039.2006.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B35 upregulates the production of endothelin‐1 in HLA‐transfected cells: a possible pathogenetic role in pulmonary hypertension

Abstract: HLA-B35 is associated with an increased risk for developing isolated pulmonary hypertension (iPHT) in systemic sclerosis, but the mechanisms underlying this association have not been fully elucidated yet. Endothelin-1 (ET-1) is the main pathogenetic molecule implied in the development of iPHT; therefore, we sought to determine if ECV304 cells transfected with the HLA-B35 allele produce increased amounts of ET-1 after incubation with physiological concentrations of interleukin-1 beta (IL-1beta). ECV304 cells tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Apoptosis is known to be an important factor in causing lymphocyte depletion in acquired AIDS patients (28) and this process is further enhanced by the class I overexpression that is induced in tissues during viral infections. Our previous studies suggested that the upregulation of endothelin-1 (ET-1) in activated HLA-B35–positive endothelial cells (ECs) (29) may be the basis of the association between HLA-B35 allele and the isolated pulmonary hypertension (iPHT) in Italian scleroderma (SSc) patients (30, 31). However, the mechanisms underlying this association have not been fully elucidated.…”
mentioning
confidence: 99%
“…Apoptosis is known to be an important factor in causing lymphocyte depletion in acquired AIDS patients (28) and this process is further enhanced by the class I overexpression that is induced in tissues during viral infections. Our previous studies suggested that the upregulation of endothelin-1 (ET-1) in activated HLA-B35–positive endothelial cells (ECs) (29) may be the basis of the association between HLA-B35 allele and the isolated pulmonary hypertension (iPHT) in Italian scleroderma (SSc) patients (30, 31). However, the mechanisms underlying this association have not been fully elucidated.…”
mentioning
confidence: 99%
“…C. pneumoniae-infected monocyte cells are shown to up-regulate many genes including the vasoconstrictor endothelin 1 (41). HLA-B*35 influences the upregulation of endothelin 1, providing an explanation for the epidemiological association existing between isolated pulmonary hypertension and HLA-B*35 (38).…”
Section: ) Nsmentioning
confidence: 99%
“…The HLA-B*35 allele has been shown to confer a significant proapoptotic influence to different kind of cells. It may promote pathological cell activation and proliferation and gene transcription through the control of the intracellular cation concentration (38). C. pneumoniae-infected monocyte cells are shown to up-regulate many genes including the vasoconstrictor endothelin 1 (41).…”
Section: ) Nsmentioning
confidence: 99%
“…The association with HLA-B*35 had already been described, and this allele appears to be involved in the upregulation of ET-1 and the pathogenesis of PAH [27, 28]. Gladman et al found a significant association between PAH and the HLA-A*30, B*13, B*65, and DRB1*03 alleles [4].…”
Section: Discussionmentioning
confidence: 99%
“…Some class I alleles were also related, such as A*30, B*13, B*65 [4], and B*35, which appear to play a role in the production of endothelin-1 (ET-1) in SSc [27, 28]. HLA-DRB1*01, DRB1*03, and DQB1*0501 were also related to PAH and ACA [29, 30].…”
Section: Introductionmentioning
confidence: 99%